(untitled) (Medico Legal Update, 2020)
Objective: Assess the severity of mood disorders in adolescents with type 1 diabetes mellitus (TIDM), and identify the relationship between the mood disorder and some socio-demographic characteristics among Adolescents. Methodology: A descriptive study was carried out at center of diabetics & endocrine disease in the Kirkuk city, from February, 10th, 2019 up to November 10th, 2019 in order to achieve the objectives of the present study. Non-Probability (Purposive) sample of (70) patients. Developed questionnaire was constructed for the purpose of the study which consisted of two parts: the demographic characteristics; and Child Depression Inventory (CDI) it is a Likert-type scale consisting of 27 items . The data were collected through the use of interview technique (face to face). The data was analyzed through the application of descriptive statistical analysis (Frequency, Percentage (%), Mean of Score) and inferential statistic (ANOVA & t. test). Results: The findings of the study indicated that the majority of the sample (40%) of them with age group (16-17 years), (54%) of them were male, (71%) of them single, the most of the sample were graduated from intermediate school (47%), regarding to the occupation (42.9%) of the sample was student, and in relation to financial status the majority of the adolescent was in barely sufficient and constitute (77%).